Competing Developmental Demands Among Suicide-Bereaved Emerging Adults. (May 2020) - Mead, Jessica
This qualitative group case study was ascertained to conceptualize theory on the topic of grief and emerging adulthood. A literature review proved no research to this specific experience. The aim of this study was to understand the suicide grief experience in this developmental stage. Based on the exploration of 150 suicide-bereaved emerging adults, participants in the Catholic Charities Young Adult Support Group expressed common themes related to the their unique grief experiences. Criterion sampling was used, as all these individuals voluntarily attended this group after losing a loved one to suicide. The methodology was observation and recording of oral data, and participants were asked to provide quarterly program evaluations. The analysis of data was recorded based on observed themes of statements made by participants. The conceptualized grief experiences that underpin this stage of development appear to work in opposition with grief tasks. This population would benefit from further research.